Changing the Narrative of Nature: Towards Sustainability - Mukherjee , Atreyee (Problemy Ekorozwoju, 2023)
Nature, an ontologically dynamic entity, has been the object of different types of conceptualizations. In recent types, it has been metaphorically conceptualized as a resource. This conceptualization is problematic such that it reduces the dynamic interdependent nature to a mere store-house for materials. This leads to the conceptualization that humans can use nature up until stock lasts. On top of that, our hunting-gathering instincts have made us reckless consumers and hoarders of things we think are necessary. This non-sustainable behavior is detrimental to our nature which holds us, nurtures us, and provides for us. To change the narrative of nature in the world of sustainability, sustainable development and sustainable practices, we must change our conceptualization of nature. In the present work, we present the problematic conceptualization of nature as a resource. We also discuss certain conceptualizations and their impact in the discussions on sustainability. And finally, we provide a linguistic alternative to the metaphoric conceptualization of nature that has the potential to alter the non-sustainable practices and take society towards sustainability.